Plasmid-Mediated Fluoroquinolone Resistance Genes in Quinolone-Susceptible Aeromonas spp. Phenotypes Isolated From Recreational Surface Freshwater Reservoir - Kosikowska, Urszula; Stec, Joanna; Andrzejczuk, Sylwia; Mendrycka, Mariola; Pietras-Ożga, Dorota; Stępień-Pyśniak, Dagmara (Frontiers in Cellular and Infection Microbiology, 2022)
Aeromonas spp. are recognized as opportunistic pathogens causing diseases. Infections in humans can result mainly in gastrointestinal and wound diseases with or without progression to septicemia. Although Aeromonas spp. are not known uropathogens and they rarely cause urinary tract infection, we hypothesize that the presence of these bacteria in the water and the contact during, e.g., recreational and bathing activity can create the conditions for the colonization of the human body and may result to diseases in various locations, including the urinary tract. Our study presents the occurrence of aeromonad fluoroquinolone-susceptible phenotypes with the presence of plasmid-mediated fluoroquinolone resistance (PMQR) genes in a natural freshwater reservoir occasionally used for recreational activities. Sixty-nine isolates collected during the bathing period were identified by mass spectrometry and screened for the presence of fluoroquinolone-resistant phenotypes and genotypes. Fluoroquinolone susceptibility was determined as minimal inhibitory concentration values. PMQR qnr genes were detected by PCR. Isolates comprising eight species, namely, mainly Aeromonas veronii (50.7% isolates) and Aeromonas media (24.6% isolates) and rarely Aeromonas eucrenophila, Aeromonas caviae, Aeromonas bestiarum, Aeromonas ichthiosmia, and Aeromonas hydrophila, were selected. All isolates were phenotypically susceptible either to ciprofloxacin or levofloxacin. Unexpectedly, at least one to three of the PMQR genes were detected in 42.0% of the fluoroquinolone-susceptible Aeromonas spp. phenotypes. Mainly the qnrS (34.8% isolates) and qnrA (14.5% isolates) determinants were detected. In conclusion, the freshwater reservoir occasionally used for bathing was tainted with aeromonads, with a high occurrence of opportunistic pathogens such as A. veronii and A. media. MALDI‐TOF MS is a powerful technique for aeromonad identification. Our data reveals the mismatch phenomenon between fluoroquinolone-susceptible aeromonad phenotypes and the presence of plasmid-mediated qnr resistance genes. It suggests that phenotypically susceptible bacteria might be a potential source for the storage and transmission of these genes. The exposure during, e.g., a recreational activity may create the potential risk for causing infections, both diagnostically and therapeutically difficult, after expressing the resistance genes and quinolone-resistant strain selection.